2014
DOI: 10.1105/tpc.114.128439
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the BBAA Component of Bread Wheat during Its History at the Allohexaploid Level

Abstract: Subgenome integrity in bread wheat (Triticum aestivum; BBAADD) makes possible the extraction of its BBAA component to restitute a novel plant type. The availability of such a ploidy-reversed wheat (extracted tetraploid wheat [ETW]) provides a unique opportunity to address whether and to what extent the BBAA component of bread wheat has been modified in phenotype, karyotype, and gene expression during its evolutionary history at the allohexaploid level. We report here that ETW was anomalous in multiple phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 84 publications
4
93
0
Order By: Relevance
“…The presence of the Ph1 locus on the 5B chromosome, which prevented homeologous exchanges, likely contributed to the high karyotype stability of the restituted wheat (Zhang et al 2014). Theoretically, the extracted genome should be .99.8% identical to the A a A a B a B a subgenomes of its bread wheat donor after the ninth backcrossing (Zhang et al 2014). Although the extracted AABB genomes would largely represent those in bread wheat, the minor part of the genomic composition of the extant tetraploid still retained could make them diverge from the original situation to certain extents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of the Ph1 locus on the 5B chromosome, which prevented homeologous exchanges, likely contributed to the high karyotype stability of the restituted wheat (Zhang et al 2014). Theoretically, the extracted genome should be .99.8% identical to the A a A a B a B a subgenomes of its bread wheat donor after the ninth backcrossing (Zhang et al 2014). Although the extracted AABB genomes would largely represent those in bread wheat, the minor part of the genomic composition of the extant tetraploid still retained could make them diverge from the original situation to certain extents.…”
Section: Discussionmentioning
confidence: 99%
“…The normal growth and vigor of resynthesized B. napus parented by RBR (data not shown) further proved the correction of the altered functions of the AA subgenome by the CC subgenome. Similarly, the extracted tetraploid wheat (A a A a B a B a ) with a stable karyotype exhibited the wide-ranging phenotypic abnormalities (Kerber 1964;Zhang et al 2014), and many (rather than a few) genes were likely affected in its genome. But the resynthesized allohexaploid wheat parented by extracted tetraploid wheat fully restored normal phenotypes and high fertility, which also demonstrated that the DD subgenome compensated for the compromised functionality of the BBAA subgenomes of bread wheat (Kerber 1964;Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations